Business Intelligence in Non-Governmental Organisations in Barbados - Caddle, Katharine (Universidad ESAN, 2016)
The twenty-first century is witness to data exchange at alarming quantities and rates along with a variety of data types from multiple sources. This situation is coupled with an everincreasing connectivity of devices and of the people who use them. Business intelligence and analytics (BI&A) concepts have arisen as ways of exploiting this plethora of data to extract insights thus improving and accelerating decision-making in a number companies. However, such decision support systems have traditionally been utilised by profit-focused commercial entities with limited regard for how BI&A can benefit the non-governmental sector. This study addresses the previous dearth of research related to intelligence and analytics adoption by non-governmental organisations (NGOs). We identify the main data management needs of NGOs and juxtapose those requirements with the features of BI&A. Barbados is used as a case study with investigation of the current data management practices and attitudes within some societal development non-governmental organisations of that Small Island Developing State.
Keywords: Inteligencia empresarial; Desarrollo social; Organizaciones no gubernamentales; Sistemas de soporte a la decisión; https://purl.org/pe-repo/ocde/ford#5.02.04